Application of Spatial Methods in Predicting Electricity Demand Based on Small Islands in Sebatik Island Divided by Two Countries - Wijaya, I Gede Putu Oka Indra; Marsuki, Aminah Indahsari (UIR PRESS, 2025)
Indonesia, as the largest archipelagic country in the world, also has several outer islands. Sebatik Island is one of the 92 outer small islands of Indonesia, located in a strategic position as it borders Malaysia. Various needs of society, one of which is electricity, are very important for people's lives and economic development. Thus, the goal is for all households in Indonesia to have access to electricity by 2024, with both the electrification rate and the ratio of electrified villages reaching 100%. An electricity plan is also necessary to help ensure that electricity is distributed fairly and equitably throughout Indonesia. Load prediction is an essential aspect of the load side of the electric power system that requires careful planning. Machine learning methods are not suitable for application in load prediction analysis in remote areas of small islands, which have limited space. Therefore, this research presents an alternative approach, specifically the spatial method utilizing (RTRW) documents. The application of this spatial method is intended to offer an overview of electricity load predictions that are more aligned with the actual situation. This spatial method analyzes the area size with land use development patterns according to local policies, multiplied by the standard definition of an activity in each spatial unit. Thus, an estimate of the peak load for each year is obtained, even up to ultimate conditions. The load prediction model follows the Gompertz equation, where the ultimate condition obtained is 63.55 MW, which may occur 118 years from the starting point in 2022. Choosing a 90% confidence level in the Monte Carlo simulation provides a reasonable range of predicted values. Based on this new knowledge, a country's electric utility will be able to build infrastructure and generate electricity in a more efficient manner.